Repercusión del saber local en el manejo y conservación del suelo en los cantones Catamayo y Saraguro en la provincia de Loja - Bermeo Torres, Maria Fernanda (2018)
Abstract: Local knowledge in agricultural production evolves over time, and as a function of climatic, edaphic of culture, social and economic characteristics; that is why this work gives a boost to local knowledge in the management and conservation of soils; those that were analyzed in the cantons of Catamayo and Saraguro of the province of Loja: By means of surveys applied at random to 18 families of the different parishes of each canton. Questions about soil fertility and fertility indicator plants, soil fertility indicators and acquired knowledge about soil management were asked. With the obtained data, we proceeded to contrast with scientific information, obtaining as a result the identification of species that develop in fertile and infertile soils; In addition, the main physical, biological and production characteristics for the identification of fertile and infertile soils were determined, as well as information was obtained on the origin of the acquired knowledge, the way of managing the soils and how the quality of the soil has changed through time.